Modular Megaprosthesis as a Definitive Salvage Strategy for Recalcitrant Distal Femoral Non-Unions: A Biological and Mechanical Reset in the Hostile Environment - Mujaddid Idulhaq; Fajar Baskoro Gardjito; Agil Murthala (HM Publisher, 2026)
Background: The management of recalcitrant distal femoral non-unions characterized by massive bone loss and exhausted biological potential presents a formidable challenge in orthopedic surgery. This study evaluates the early functional outcomes and safety of modular knee megaprostheses as a radical salvage strategy, utilizing oncologic reconstructions as a benchmark for comparative analysis. Methods: A descriptive case series of eight consecutive patients, including six oncologic and two non-oncologic cases, was conducted between December 2022 and March 2025. Non-oncologic cases involved elderly patients with a mean age of 48.5 years and multiple failed prior fixations. A standardized infection rule-out protocol was strictly applied, involving serological markers and joint aspiration. Functional outcomes were quantified using the Musculoskeletal Tumor Society (MSTS) score with a mean follow-up of 14.8 months. Results: The mean MSTS score across the cohort was 20.2 out of 30. Non-oncologic patients demonstrated lower physical performance scores, averaging 18.5 compared to 20.8 in the oncologic group, primarily due to long-standing disuse atrophy and age-related confounders. However, these patients reported significantly higher emotional acceptance, averaging 4.5 out of 5, following the immediate restoration of limb stability. No acute periprosthetic infections or mechanical failures were observed within the short-term follow-up period. Conclusion: Megaprosthesis serves as a viable biological and mechanical reset for complex non-unions, converting a failed biological healing process into a reliable mechanical solution. While the procedure requires rigorous infection screening and carries long-term risks, it offers immediate stability and transformative pain relief in elderly or multiply-operated patients.